Studies on Pyrrolidinones: Chemistry of Dimethoxytriazines - Lucescu, Liliana; Gautret, Philippe; Oudir, Souhila; Rigo, Benoît; Belei, Dalila; Bîcu, Elena; Ghinet, Alina (Synthesis, 2013)
The synthesis of dimethoxytriazine-containing N-aryl substituted pyrrolidinones is realized for the first time. Three new modes of reactivity for these substrates possessing a 4,6-dimethoxy-1,3,5-triazine unit are discussed. Their treatment with acid leads to complete O-demethylation of the methoxy groups, while similar reaction in a basic medium leads to partial O-demethylation. In contrast, heating in the presence of dimethyl sulfate as the catalyst induces migration of the methyl groups from the oxygen atoms to the triazine nitrogens (Hilbert–Johnson transposition). These new scaffolds may demonstrate biological potential.
Keywords: arylation; cleavage; carboxylic acids; zinc; ring closure